(untitled) (Proceedings of International Conference on Special Education, 2017)
Language is, but not exclusively a tool for communication and this includes sign language. Sign language is an essential tool for deaf community to communicate and is often community-specific. At the local level, it is noticed that the main issue of creating a sustainable inclusive society lies in the wide spread of the significance of sign language. The gap between the hearing and hearing- impaired remains open, with effective leadership and universal access to public amenities remain constant. Consequently, this paper explores the general local landscape of Kuching (capital of Malaysian state of Sarawak), identifying existing policies and practices that can be leverage on for a more sustainable inclusive society for the deaf. The paper also proposes the replicating successful movement campaign such as #whyisign that could increase inclusion and success in building an inclusive society.